Prevalence of Maxillary Central Incisor Impaction and Supernumerary Teeth among Nepalese Orthodontic Patients - Kafle, Dashrath; Shrestha, Sita; Acharya, Nisha; Agarwal, Aaradhana (Orthodontic Journal of Nepal, 2015)
Introduction: Very few studies have been done on impacted maxillary central incisors and supernumerary teeth. Objective: To find the prevalence of maxillary central incisor impaction and supernumerary teeth among orthodontic patients attending Dhulikhel Hospital, Kathmandu University Teaching Hospital. Materials & Method: The retrospective study consisted of 787 records of orthodontic patients of age 10-35 years. Dental model and orthopantomograph were retrieved and searched for impacted maxillary central incisors and supernumerary teeth. Incomplete records and patients with known syndromes were excluded from the study. Descriptive statistics was applied to find the prevalence rate and comparison between male and female was done by chi-square test. Result: Out of total samples, 14(1.8%) and 11(1.4%) samples were found to have impacted maxillary central incisors and supernumerary teeth respectively. There was no significant difference in prevalence of impacted maxillary central incisors between male and female samples (p=0.78), however there was significant difference in occurrence of supernumerary teeth between gender groups (p=0.025). Conclusion: The prevalence of impacted maxillary central incisor and supernumerary teeth among orthodontic patients attending Dhulikhel Hospital, Kathmandu University Teaching Hospital is 1.8% and 1.4% respectively. Male patients have higher chance of having supernumerary teeth than female patients